SAVING ENERGY IN VENTILATION AND AIR CONDITIONING SYSTEMS - M.R., Ismanxodjayeva (International Journal of Psychosocial Rehabilitation, 2020)
The peculiarity of microclimate support systems is that they consume a large number of energy resources, including thermal and electric energy and tap water. The problem of reducing energy consumption by ventilation (HV) and air conditioning (SLE) systems, as part of the general problem of efficient energy use, is especially relevant in the highly continental conditions of the Republic of Uzbekistan.A quantitative assessment of the energy efficiency of microclimate facilities is based on the total annual energy consumption of the systems. Annual energy consumption appears to be the most objective energy indicator, since it is in the annual cycle that all energy consumption modes are fully manifested.With SK equipment, the determination of the annual heat or cold consumption of SV or SCR is reduced to the integration of the power consumption of the equipment depending on the season. The latter value is a function of the heat content of the outdoor air, because heat and artificial cold are only used to process the outdoor air. Among the variety of models representing the annual change in the parameters of the outdoor air, we distinguish two groups. The first type of models is based on a description of the annual course of monthly average parameters. Models are presented in tabular form or described analytically. A variation of this model of the external climate is the so-called representative year, the use of which has become widespread abroad.